Project sustainability in the conditions of digitalization - M. V. Lubenets; S. M. Sycheva (Вестник университета)
The methodological basis of the study is fundamentals of the project sustainability concept, key principles and features of sustainable development, conceptual approaches to strategic sustainability of project activities. A content analysis of Russian and foreign literature was carried out to determine the current challenges of project implementation. The article uses general scientific methods of analysis, synthesis, generalization, decomposition of factors, as well as tabular and graphical visualization techniques of various categories. The results of the paper consist in clarifying the theoretical aspects of the projects’ sustainability and their constituent elements, in substantiating high level of uncertainty of various criteria for project implementation due to the significant turbulence of external factors and the emergence of new challenges, as well as in determining the need to transform established approaches to the sustainable development of projects. As a result of the research, a new approach has been developed to assess the sustainability of projects based on a strategic model that takes into account modern challenges of uncertainty and turbulence. The study prospects lie in practical use of developed integrated approach for models’ formation for the sustainable implementation of projects in various business areas.